Lack of an Effect of Ritonavir Alone and Lopinavir-Ritonavir on the Pharmacokinetics of Fenofibric Acid in Healthy Volunteers - Gordon, Lori A. (Pharmacotherapy, 2016)
STUDY OBJECTIVE: As we previously observed a significant 41% reduction in gemfibrozil exposure after 2 weeks of lopinavir-ritonavir administration, we sought to determine the influence of lopinavir-ritonavir and ritonavir alone on the pharmacokinetics of fenofibric acid, an alternative to gemfibrozil for the treatment of elevated triglyceride levels. DESIGN: Open-label, single-sequence pharmacokinetic study. SETTING: Clinical Research Center at the National Institutes of Health. SUBJECTS: Thirteen healthy adult volunteers. INTERVENTION: Subjects received a single oral dose of fenofibrate 145 mg during three study phases: before ritonavir administration, after 2 weeks of administration of ritonavir 100 mg twice daily, and after 2 weeks of administration of lopinavir 400 mg–ritonavir 100 mg twice daily. MEASUREMENTS AND MAIN RESULTS: Serial blood samples were collected over 120 hours for determination of fenofibric acid concentrations. Fenofibric acid pharmacokinetic parameter values were compared before and after concomitant ritonavir or lopinavir-ritonavir administration. The geometric mean ratios (90% confidence intervals) for fenofibric acid area under the plasma concentration–time curve were 0.89 (0.77–1.01) after 14 days of ritonavir alone compared with baseline (p>0.05) and 0.87 (0.69–1.05) after 14 days of lopinavir-ritonavir compared with baseline (p>0.05). Study drugs were generally well tolerated; all adverse events were mild or moderate, transient, and resolved without intervention. CONCLUSION: In contrast to a significant interaction between gemfibrozil and lopinavir-ritonavir, neither lopinavir-ritonavir nor ritonavir alone altered the pharmacokinetics of fenofibric acid in healthy volunteers. These data suggest that fenofibrate remains an important option in human immunodeficiency virus–infected patients receiving common ritonavir-boosted therapy.